2D covalent organic framework: a photoactive heterogeneous catalyst for chemical fixation of CO2 over propargyl amines in water under sunlight. (August 2021) - Sarkar, P.; Hazra Chowdhury, A.; Biswas, S.; Khan, A.; Islam, S.M.
Abstract: We have demonstrated the efficient synthesis of Pd(II)-based 2D mesoporous covalent organic framework (COF) along with a small amount of Pd(0), which is characterized by different characterization tools. These studies suggest that this material with low bandgap energy (Eg) of 1.73 eV can exhibit great photocatalytic activity toward CO2 fixation reaction. Therefore, we have applied the Pd(II)-loaded COF as a new and effective photocatalyst for the preparation of oxazolidinone through the chemical fixation of CO2 . The reaction takes place in green solvent (H2 O) in absence of any base and under the sunlight at atmospheric pressure of CO2 without using any cocatalyst. The reaction does not happen in the dark. In this context, we showed that a turnover number (TON) of 3.392 × 10 3 can be achieved using the catalytic cycle under sunlight. The light dependency of the reaction is also checked by a control experiment via light modulation between light on and off. Furthermore, the catalyst shows efficient reusability for multiple reaction cycles, and also the heterogeneity test of the material suggests minimal active metal leaching during the catalysis reaction cycles. These results for the photocatalytic synthesis of oxazolidinone by CO2 incorporation over COF under sunlight open a new environment-friendly green pathway for the formation of oxazolidinones. Graphical abstract: Image 1